The Development of Overhead Pass Learning Models in Volleyball - Destriana Destriana; Muslimin Muslimin; Destriani Destriani (Universitas PGRI Palembang, 2021)
This study aims to develop a learning model of passing volleyball for class VIII junior high school students. This study uses research and development research methods with the ADDIE model (Analysis, Design, Development or Production, Implementation or Delivery and Evaluations). The subjects in this study were students of SMP N 1 Palembang Class VIII class 2018/2019. Qualitative and quantitative data analysis techniques. This research was conducted up to the development stage, namely large-scale trials. The validation of this model of passing was carried out by experts in phycical education, volleyball game experts, and linguists. The results of the model validation (Design stage) of this top learning model obtained a percentage of 87.5% of PJOK experts, 90% of volleyball game experts, and 87.5% of linguists from the results of expert validation show that the learning model is the top volleyball game Valid or worth using. The development stage consists of one-on-one evaluations, small group trials, and large group trials. The results of the large group trial were obtained using the instrument of the upper pass motion assessment process, the percentage was 12.5% or 3 students were very good, 87.5% of students got good grades or as many as 21 students. Based on large group trials, the product in the form of a learning model for volleyball can be used in the volleyball learning process.